Critical Analysis of Public Health Campaigns, Behavioral Impacts, And Digital Strategies in Outreach - Al ishaq, Alhassan Mohammed Ahmed; Al Ishaq, Ebrahim Mohammed Ahmed; Al Alhareth, Saleh Saeed; Al khaywany, Hassan mohmed Ali; Almurdif, Hsaan Saad; ALYami, Abdullah Ali Saeed; Almurdif, Mohsen Ali Mansour; Albalwi, khadra Abdullah Basher; Alyami, Salem Nasser Hamad; Alhadi, Tarek Masod Bajjash (Journal of Ecohumanism, 2024)
Health promotion campaigns have taken the central stage of comprehensive approaches toward enhancing the world’s health quality. Due to growing technological advancement, the point of health care and awareness has embraced media technology instead of conventional media technology, thus availing a wider and more diverse coverage. This paper critically evaluates some public health advertisement crusades, the changes in the behaviors of the target groups, and how the use of digital methods can help boost public health communication efforts. Specifically, this paper explores the literature on the difficulties, achievements, and emerging patterns in establishing public health promotional campaigns and interventions, reflecting on behavioral change theories, social media promotional campaigns and mobile health applications, and adopting digital strategies in public health promotions. The assessment also uses case studies and findings in figures and tables to provide recommendations for enhancing subsequent campaigns.